2020
DOI: 10.1021/acsami.9b22559
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Precipitation of Cluster and Acicular Hydroxyapatite onto Porous Poly(γ-benzyl-l-glutamate) Microcarriers for Bone Tissue Engineering

Abstract: Bone tissue engineering scaffold based on microcarriers provides an effective approach for the repair of irregular bone defects. The implantation of microcarriers by injection can reduce surgical trauma and fill various irregular shaped bone defects. Microcarriers with porous structure and osteogenic properties have shown great potential in promoting the repair of bone defects. In this study, two kinds of hydroxyapatite/poly-(γbenzyl-L-glutamate) (HA/PBLG) microcarriers were constructed by emulsion/in situ pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…Nowadays, the hydroxyapatite (HAp), which is produced by biomimetic mineralization process using simulated body fluids (SBFs), has become the most popular bone substitute material attributing to the similarity in the inorganic component of human and animal bones, good biocompatibility, osteoconductivity, and osteoinductivity [ 4 , [14] , [15] , [16] ]. The crystalline structure and morphology of HAp play vital roles in mediating cellular behaviors [ [17] , [18] , [19] , [20] ]. For instance, the crystalline structure of HAp affects the release process of Ca and P ions, which regulate the cell fate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, the hydroxyapatite (HAp), which is produced by biomimetic mineralization process using simulated body fluids (SBFs), has become the most popular bone substitute material attributing to the similarity in the inorganic component of human and animal bones, good biocompatibility, osteoconductivity, and osteoinductivity [ 4 , [14] , [15] , [16] ]. The crystalline structure and morphology of HAp play vital roles in mediating cellular behaviors [ [17] , [18] , [19] , [20] ]. For instance, the crystalline structure of HAp affects the release process of Ca and P ions, which regulate the cell fate [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the crystalline structure of HAp affects the release process of Ca and P ions, which regulate the cell fate [ 19 ]. The morphology of HAp can provide biophysical information for adjusting cell behaviors [ 18 ]. In addition, the roughness surfaces of HAp can facilitate cell adhesion and proliferation [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyapatite (Ca 10 (PO 4 ) 6 (OH) 2 ; HAp), the main component of human bones and teeth, is known as a bioceramic and is commonly used as an artificial bone and tooth root [ 1 , 2 ]. Artificial bones put to practical use in the medical field have various forms and shapes, such as granules [ 3 ], blocks [ 4 ], cylinders [ 5 ], porous bodies [ 6 ], and paste (cement) [ 7 , 8 , 9 ], and suitable ones are selected depending on the application.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, hydroxyapatite (HA; Ca5-[PO4]3] OH]) and beta-tricalcium phosphate (β-TCP; Ca3[PO4])2) have been widely applied to facilitate bone repair and regeneration in clinical settings due to their recognized biocompatibility and osteoconductivity (15,16). Previous studies have also shown that single-phase materials cannot perfectly meet the needs of BTE scaffolds (17).…”
Section: Introductionmentioning
confidence: 99%